Mopane worms (Imbrasia belina) as indicators of elemental concentrations in a trophic system - Pillay, Sumeshni (My University, 2016)
The impacts of mining on the environment continue to pose a risk in many regions. Palabora Mining Company (PMC) situated in Limpopo Province, South Africa is of environmental interest because of its shared border with South Africa’s Kruger National Park. PMC generates both gaseous (emitted from the reverberator (Rev; also known as a smokestack)) and solid (stored in the tailings storage facility (TSF)) waste products. To assess possible pollution to the environment from PMC’s activities, two study species were chosen, the Anomalous Emperor Moth (Imbrasia belina [Westwood 1849] (Lepidoptera: Saturniidae)) and its primary host the mopane tree (Colophospermum mopane [Kirk ex Benth.]). In addition to these two species being abundant on and around PMC, the mopane moth and all stages of its lifecycle are a source of food to many animals, and mopane caterpillars are a valuable source of food and income to many people in this region. Mopane caterpillars and mopane leaves were collected from on and around PMC at varying distances from the reverberator and TSF, as well as from several control sites. The elemental contents of these samples were analysed for 25 elements, focusing on copper, iron, aluminium, silicon, arsenic, zinc, nickel, lead, mercury, chromium and cadmium. In addition to these elemental analyses, the carbon and nitrogen isotopic compositions of these samples as well as caterpillar headwidth, body mass and mandible wear were also measured to assess the impacts of elemental concentrations on caterpillar growth. No mopane caterpillars were found at the two reverberator sites closest to the reverberator itself. Overall these two reverberator sites appear to be most contaminated, as concentrations of 14 of the 25 elements measured were highest in the mopane leaves from these two sites. The copper concentrations at these two sites, 42 ppm and 29 ppm respectively, were at levels that are considered toxic to plants. Assuming that 10 mopane caterpillars (each weighing 5g) are consumed a day, copper concentrations in the mopane caterpillar bodies across sites (between 8 ppm and 12 ppm) would equate to a maximum of 0.56 mg.day-1, which is less than the recommended maximum intake level of 10 mg.day-1 suggested for humans. As there was little difference between sites in terms of leaf carbon and nitrogen composition, elemental concentrations do not appear to be affecting the nutritional content of the leaves. This would suggest that caterpillar growth is not affected by elemental concentrations at sites where they can survive. Similarly, caterpillar headwidths did not vary greatly between sites for each instar, suggesting that elemental concentrations are not affecting mopane caterpillar growth. Headwidths and mandible wear were found to be useful tools to age mopane caterpillars within an instar, and can be used in future to ascertain if mopane caterpillars are bioaccumulating elements or eliminating excess elements when they moult.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa, in fulfilment of the requirements for the degree of Master of Science. August 2015
Keywords: Mopane worm--South Africa--Limpopo.; Environmental pollution.; Leaves--Environmental aspects.; Pollution--South Africa--Palaborwa mining.